Ingested microscopic plastics translocate from the gut cavity of juveniles of the ascidian Ciona intestinalis. Issue 1 (1st January 2019) - Messinetti, S.; Mercurio, S.; Scarì, G.; Pennati, A.; Pennati, R.
Abstract: Small plastic particles, named microplastics, are abundant in the marine environment and can be ingested by marine organisms. Species with different feeding strategies can be differently affected by the presence of microplastics. Moreover, the impact of these particles can depend on their size. In this study, we analyzed the effects of 1 µm polystyrene particles on larval and juvenile development in the ascidian Ciona intestinalis . As previously reported for 10 µm beads, smaller particles caused a delay in the growth of juveniles, even if this delay was registered only at the highest concentration tested. Instead, larval development was not affected by the presence of microplastics. Histological analysis of juveniles revealed that 1 µm particles, after ingestion, can translocate from the gut to the hemocoelic cavity in just 8 days. As a defense mechanism, plastic spheres can also be phagocytized from specific circulating cells with phagocytic activity. Microplastics confirmed their potential as a threat to marine wildlife, interfering with food uptake and growth.